Sociodemographic determinants of HPV vaccine awareness, uptake, and intention among parents of adolescents in France 2021-22 - Alexia F. Rivera; Josée M. Dussault; Damien Oudin Doglioni; Sandra Chyderiotis; Jonathan Sicsic; Anne-Sophie Barret; Jocelyn Raude; Aurélie Gauchet; Amandine Gagneux-Brunon; Sébastien Bruel; Morgane Michel; Anne-Sophie; et al. (Taylor & Francis Group, 2024)
Human Papillomavirus (HPV) vaccine coverage was <50% in France in 2022 and even lower among socially disadvantaged populations. We aimed to evaluate socio-demographic determinants of HPV vaccine awareness, uptake, and intention among parents of adolescents, and related attitudes and knowledge items. Parents of adolescents attending middle schools across France, who participated in a randomized trial responded to an anonymous baseline survey, conducted between November 2021 and February 2022. We used logistic regression models adjusting for a child's age and sex to explore sociodemographic determinants (including at-home multilingualism, occupational categories, local deprivation index and urbanity) of HPV vaccine awareness, uptake, and intention. Among the 1889 participants from 61 schools, parents working as factory workers/farmers had significantly lower odds of vaccine awareness compared to executives/professionals, both if they reported (OR = 0.07; 0.03-0.15) or not (OR = 0.20; 0.11-0.36) speaking also another language than French at home. Parents in lower occupational categories with multilingual families were less likely to have the intention to vaccinate their child (OR = 0.19; 0.07-0.56). Recent physician visit or vaccine offer was strong positive determinants of awareness, uptake and intention. A substantial gradient across occupational categories was observed for attitudes and knowledge around HPV vaccine usefulness, safety, and accessibility. This study confirms the disparities on HPV vaccine uptake in France and provides insight into mechanisms of social disparities in HPV vaccine awareness, access and intention.